A Bus-based Opportunistic Sensing Network - Caminha, Pedro Henrique Cruz; Costa, Luís Henrique Maciel Kosmalski; Couto, Rodrigo de Souza (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2021)
Smart city applications need data about the city, and this data must follow specific requirements. Two of these requirements are the maximum delivery delay and the minimum measurement frequency. Using buses to gather data and bus stops as gateways can be cost-effective, but data might not fit the application requirements. In this thesis, we present a model to minimize the delay of data delivery, a metric to estimate the coverage, and a prototype of the nodes of such a network. We use GPS data from the bus ﬂeet of Rio de Janeiro to show that it is possible to cover a significant part of the city, fulfilling application requirements specified by the smart city literature.